Regulating nitrogenous adsorption and desorption on Pd clusters by the acetylene linkages of hydrogen substituted graphdiyne for efficient electrocatalytic ammonia synthesis. (August 2021) - Guo, Ying; Liu, Jianwen; Yang, Qi; Khemthong, Pongtanawat; Huang, Zhaodong; Zhao, Yuwei; Chen, Ze; Dong, Binbin; Fu, Xian-Zhu; Luo, Jing-Li; Zhi, Chunyi
Abstract: Precious metal Pd has the intrinsic superiority in adsorbing N2 molecule and wrecking the high cleavage barrier of the N≡N bond, however, its over-strong adsorption ability is unfavorable to the desorption of the produced NH3 during the electrochemical N2 reduction (NRR), which weighs heavily against the NH3 productivity. Here we demonstrate that the high electron-density of acetylene linkages of hydrogen substituted graphdiyne can regulate the nitrogen adsorption and NH3 desorption on the active Pd sites (Pd/HsGDY), resulting in impressive electrocatalytic NRR performance. The optimized Pd/HsGDY features an ultrahigh Faraday efficiency of 44.45% and an NH3 yield of 115.93 mg g −1 h −1 (or 11.59 µg cm −2 h −1 ). Density functional theory calculations reveal that the acetylene linkages in HsGDY can tune the d band center of active Pd atoms by downward shifting it from the Fermi level. This favors the hydrogenation of nitrogen on HsGDY-tuned Pd sites and benefits the desorption of produced NH3 from the catalyst surface to recover active sites induced by heat dissipation during the exothermic hydrogenation processes, resulting in a selectively facilitated electrosynthesis of NH3 . Graphical Abstract: ga1 Highlights: HsGDY offers abundant space to effectively anchor the Pd atoms and in-situ grow the Pd nanoclusters. Acetylene linkages moderate the adsorption and desorption capability of active Pd sites for the NRR intermediates. The electron accumulation and electron depletion occur in Pd-HsGDY interfaces facilitating the NRR.